Clinical practice guide for the care to children and adolescents with chronic renal disease - Jorge Félix Rodríguez Ramos; Guillermo Luis Herrera Miranda (Centro Provincial de Información de Ciencias Médicas, 2024)
Chronic renal disease constitutes a health problem due to its impact on individuals, society and economy. Taking into account the above-mentioned, and after a wide literature search, a clinical practice guide was designed in Luis Augusto Turcios Lima Polyclinic from Pinar del Río province, directed to primary health care professionals, aimed at improving the life quality of children and adolescents with this disease. It was elaborated by medicine methods based on the evidence, according to the consent and opinion of experts. It was possible to generalize this tool, give recommendations and up to date according to the new medical evidences. Finally, it was evaluated by experts as very recommended.